Sustainable organisation performance evaluation using balance scorecard and analytical hierarchical process - Swamy Arabinda; Mishra Sushant Kumar; Mishra R.K. (Journal of Engineering Management and Competitiveness, 2023)
The present study uses the Analytic Hierarchy Process and Fuzzy Comprehensive method to evaluate the sustainable performance index with different sustainable dimensions on organisational performance measures. Limited integration methods available, inadequate exploration of sustainable dimensions, insufficient attention to key performance indicators, and lack of comparative studies have prompted the present study. This empirical study reveals that a balanced scorecard can be effectively applied to an aerospace organisation for sustainable performance evaluation. It is essential to select proper key performance indicators for a performance measuring system. This paper presents the study carried out on the sustainable performance evaluation in an aerospace organization in the Indian context and found the sustainability of the Organisation as moderate Level. The survey also identifies the Levels of different segments such as learning and growth, internal business, social and environmental dimensions, finance, customer dimension, etc. Suggestions are also included for the improvement of levels of various segments. The paper also covers the impact of locational differences or product segments on sustainable performance.